Power and Reflection: Die Vierte Gewalt Questions a Panel of Media Protagonists (KULT_online, 2009)
The 21st century media covers everything and everyone – except itself. This volume dealing with the Fourth Power consists of conversations with 26 of the most influential print, radio, and television journalists working in Germany. In interviews with Friederike Schröter and Claus Gerlach, these luminaries discuss their personal concepts of journalism, their career histories, and individual world views.